Enhancement of Cholesterol Esterification in Macrophages by Platelets' Secretory Products - HAYASHI, Toshio; NAITO, Michitaka; KUZUYA, Masafumi; FUNAKI, Chiaki; ASAI, Kanichi; KUZUYA, Fumio (Dōmyaku kōka = The Journal of Japan Atherosclerosis Society, 1988)
Macrophages derived foam cells and platelets are found in many lesions of atherosclerosis. The object of the study is to evaluate the effect of platelets' secretory products on foam cell formation of macrophages. Firstly, we got two kinds of platelet free supernatants, which one is prepared from platelets rich plasma frozen and thawed three times (PSPα), another one from thrombin activated platelets (PSPβ). We studied whether these supernatants and other platelets' secretory products (PDGF, STA2, and SEROTONIN) enhanced macrophages lipid storage or not by using a microscale enzymatic assay system. PSPα, PSPβ and PDGF enhanced esterified cholesterol accumulation. We supposed that platelets contributed to the lipid storage of macrophages in developing atherosclerosis.